COMMUNITY READING PARK IN SORONG: A COMPARISON OF KEIK TSINAGI AND PAPUA BERBAGI - Dayu Rifanto; Jajat S Ardiwinata; Joni R Pramudia; Grace J Burdam; Pretty Christina; Wahidatul Munawaroh (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2026)
Indonesia continues to face a serious literacy challenge, with the Papua region experiencing the most severe gaps. Community Reading Parks (TBM), are grassroots effort aimed at improving literacy, yet few studies compare how they operate, especially in Eastern Indonesia. This study aims to compare two TBMs in Sorong City, Keik Tsinagi and Papua Berbagi, using a SWOT framework to understand their respective roles, capacities, and challenges. Employing a qualitative approach, data were collected through in-depth interviews, observation, and document analysis. Key informants included the founders of both TBMs, and the research was conducted over a one-month period. The findings show that Keik Tsinagi has strong infrastructure, more books, and local facilitators, while Papua Berbagi offers flexible teaching methods and strong partnerships. However, both face challenges such as limited space, unstable volunteer support, and reliance on personal funding. The study identifies two types of TBM models, one focused on infrastructure, the other on flexible learning and highlights the need for greater institutional and community support. These findings contribute to the limited research on informal education in Papua and offer practical recommendations for policymakers, NGOs, and literacy activists